Metodologias de pesquisa e avaliação da resistência de genótipos de amendoim a Spodoptera albula (walker, 1857) (Lepidoptera: Noctuidae) - Di Bello, Mirella Marconato [UNESP] (2015)
Taking into consideration the importance of Spodoptera albula (Walker, 1857) (Lepidoptera: Noctuidae) species in recent years due to the economic losses, caused defoliation in the peanut crop and the lack of rearing methodologies and research on host plant resistance information, the aim of this study was to evaluate different materials and methods aiming non-preference feeding and antibiosis of this species, using artificial diets and peanut genotypes. The assays were performed under controlled conditions (25 ± 2 ° C, 70 ± 10% relative humidity and 12 hours photophase). Initial experiments were to adjust a design methodology for S. albula. The following biological parameters were evaluated: larval, pupal and larval to adult phase duration, survival and mortality; 12 days old caterpillars weight; 24 hours old pupal weight; sex ratio; and longevity of adults, in three artificial diets, different larval densities, couples densities and cages size for oviposition (for the oviposition assay were evaluated the number of egg masses and eggs). S. albula managed to complete its life cycle in all three diets; however, the Anticarsia gemmatalis Hübner diet was the most suitable for laboratory rearing, providing faster development and higher survival rate in compare to the others. S. albula caterpillar's individualization favored its development, allowing greater weight gain and lower mortality. Cage size does not influence the number of eggs laid by the females, and the largest number of couples per cage did not favor an increase in oviposition. Possible adjustments in the chosen diet are recommended so the rearing can reach higher survival rates. As for research methodology in plant resistance the experiments evaluated the influence of these factors on the expression of non-feeding preference in runner growth habit genotypes IAC Runner 886 and straight growth habit IAC Tatu to S. albula in assays free-choice and no-choice feeding ...